Analysis of piles in residual soil from granite considering residual loads - António Joaquim Pereira Viana da Fonseca (2007)
The paper deals with the analysis of static loading tests carried out in 3 different types of piles: bored piles with temporary casing, continuous flight auger, CFA, piles (bored and CFA piles with circular section - nominal diameter Ø600 mm) and driven piles (with square section - width 350 mm). These piles were installed in the CEFEUP/ISC'2 experimental site, located in the Campus of the Faculty of Engineering of the University of Porto (Portugal), in a contact zone between the gneissic rocks and the granite mass. After a brief geological and geotechnical site characterization, the paper presents a detailed description of the piles and the instrumentation installed in two of them. Previous analyses of the test data are summed up, emphasising the difficulties in determining the residual loads resulting from the installation processes and the unloading and the reloading cycles applied to the static loading tests. This paper aims to quantify these locked-in toe residual loads, using a mathematical model - the Modified Two Straight Lines Method (MDRM) - that allows the interpretation of the pile head load-settlement curve and the determination of the shaft and toe resistances, apart from the toe residual loads. For the shaft and toe resistances, the MDRM led to consistent results with those inferred from both, the previous analysis and the extensometer measurements; the ultimate unit shaft resistance was estimated in 60 kPa. As far as the toe's residual loads are concerned, the estimated values of about 150 kN for the bored piles were also consistent with those measured but very different from that guessed in previous analysis, about 300 kN. For the driven pile, this paper arrived at an upper bound of 500 kN for the residual load and a lower bound of 60 kPa for the ultimate unit shaft resistance.